The new norm of MINDS UMP is broadcast online - Siti Nur Azwin, Zulkapri (2020)
Pekan, 18 October 2020 - A total of 30 Universiti Malaysia Pahang (UMP) students successfully implemented the Student Induction Week 2020 (MINDS '20) program which took place online from 14 to 18 October recently involving a total of 2,110 new students for the registration session 2020/2021.